A reconfigurable channel filter for software defined radio using RNS - Smitha, Kavallur Gopi (2013)
This paper presents a high-speed FIR channel filter using residue number system (RNS) whose frequency response can be reconfigured to adapt to a multitude of channel filtering specifications of a multi-standard software defined radio (SDR) receiver. The channel filters in the channelizer of an SDR extract multiple narrowband channels corresponding to different communication standards from the wideband input signal. The proposed architecture has been synthesized on TSMC 0.18 μm CMOS standard cell technology. Synthesis result shows that the proposed reconfigurable FIR channel filter, for a Digital Advanced Mobile Phone Systems (D-AMPS) example, offers speed improvement of 42% and AT complexity reduction of 26% over existing reconfigurable FIR method.